PERANAN AUDIT INTERNAL DALAM PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE PADA BANK YANG BERBADAN HUKUM PERSEROAN TERBATAS - SADLI AZHARI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Bismar Nasution2. Mahmul Siregar3. T. Keizerina Devi A The results of the research showed that the regulations concerning adequacy of National Laws on internal auditing in bank management to implement GCG (Good Corporate Governance) is adequately fulfilled and its implementation is written in some regulations. The implementation of GCG is one of the important factors to improve the performance of the company especially bank. The role of internal auditing is to prevent and detect fraud (deceit). Internal auditing evaluates the risk encountered by an organization based on auditing planning by an accurate testing. Furthermore, internal auditors can help to prevent fraud by testing and evaluating the effectiveness of the internal control. The accountability of a Director for the results of the internal auditing i.e. findings found by the auditor is taken into the Director’s consideration. the Director forwards the result repot to the Board of Commissioner with many considerations and assessment for the auditing result report and the Board of Commissioner forwards it to the Ministry of BUMN (State Owned Enterprise).Keywords: Auditing Role, Internal Auditing, Good Corporate Governance Principle